Entomofauna associated with the cultivation of creeping tomato trees under different shading meshes - Trento, Daiane Andréia; da Silva Ponce, Franciely [UNESP]; Rocha, Rafael Rosa; de Lima Toledo, Claudia Aparecida [UNESP]; Antunes, Darley Tiago; Dallacort, Rivanildo; Butnariu, Alessandra Regina; Seabra Júnior, Santino (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2023)
This study aimed to determine the effects of protected and unprotected tomato cultivation on the insect population at the order level. The creeping tomato cv. Lampião was grown on white plastic mulching during the dry season and at high temperatures. Unprotected and protected tomato cultivation under different meshes, i.e., tunnels covered with agrotextile, organza, red, silver, and black shading, were evaluated. Pitfall traps buried at ground level were used to monitor insects inside the medium. We found 16 orders and one class (Arachnid) in the cultivation of creeping tomato, totaling 6,895 individuals collected in 36 traps in an area of 385.2 m2. The orders Hymenoptera, Coleoptera, and Diptera were the most representative, with relative frequencies of 59.4%, 10.4%, and 8%, respectively. The open field cultivation had the highest number of insects collected, totaling 2,639 individuals, with the order Hymenoptera representing 72.5% of the insects collected in this environment. The environments covered with organza and agrotextile provided fewer insects, 665 and 646 individuals, respectively. The reason for this was the increased physical barrier provided by these meshes, i.e., they presented a tighter mesh. Among the tomato development stages, the fruit maturation stage showed a higher number of insects collected.
Entomofauna asociada a un cultivo de tomate rastrero bajo diferentes mallas de sombreamento
Keywords: Colored meshes; insects; organza fabric; Solanum lycopersicum